Dual-purpose Cattle Value Chain. Results of the implementation of PROGRESA in the advancement of dual-purpose cattle production chains into value chains - Centeno Zamora, Janira Damarys; Moncada Sanchez, Dani Ogdoniel; Montoya Valladarez, Selania Marina; Ruíz Hidalgo, Valleska Jamisseth (Catholic Relief Services, 2015)
This publication is the product of a participatory capitalization process facilitated by the International Center for Tropical Agriculture (CIAT) for the Program for Rural Enterprise Management, Health, and the Environment (PROGRESA, its Spanish acronym). The document was prepared by the Technical Livestock Commission, integrated by the PROGRESA partners who collaborated in this chain (ADDAC, CONAGAN, ASDENIC, La Unión, and CRS) to offer grounds for analysis and discussion, with which communication mechanisms can be built in coordination with different stakeholders to better understand the constraints and measures to be taken within the chain. It is expected that the insights and lessons shared in this document will help organizations and stakeholders to identify strategies within future proposals dealing with this topic.